Beyond ethnicity : new politics of race in Hawaiʻi - Fojas, Camilla, 1971-; Guevarra, Rudy P., Jr; Sharma, Nitasha Tamar, 1973- (University of Hawaii Press, 2018)
From the perspective of the U.S. continent, Hawai'i is a land of aloha that enjoys all manner of peace and harmony, particularly among the races and for peoples of mixed heritage. It is a tourist paradise where visitor, local and Native mingle without incident. Ethnic difference is celebrated as a sign of multicultural globalism that designates Hawai'i as the crossroads of the Pacific. The contributors of this volume reimagine these ways of thinking about Hawai'i as a model of racial and ethnic harmony. 'Beyond Ethnicity' examines the dynamic between race and ethnicity to challenge the primacy of ethnicity and ethnic difference for examining difference in the islands. This original and thought-provoking volume poses questions about the role of race in the current political configuration of the islands and in so doing, challenges how we imagine and conceptualize race on the continent.